Romantic Attachment, Internalized Homonegativity, and Same-Sex Intimate Partner Violence Perpetration Among Lesbian Women in Italy - Tognasso, Giacomo; Trombetta, Tommaso; Gorla, Laura; Ramon, Shulamit; Santona, Alessandra; Rollè, Luca (Frontiers in Psychology, 2022)
Same-Sex Intimate Partner Violence (SSIPV) among lesbian women has been underestimated until few decades ago. While the association between romantic attachment and SSIPV has been widely demonstrated, mechanisms that mediate this association and the complex relationships between romantic attachment, SSIPV, and SSIPV-specific risk factors has not been adequately investigated to date. The current study assessed the influence of romantic attachment on SSIPV perpetration among lesbian women, exploring the mediating role of internalized homonegativity within this association. Three hundred and twenty-five Italian lesbian women with a mean age of 30 years were recruited and completed the following self-report measures: the Experiences in Close Relationships-Revised (ECR-R), the Measure of Internalized Sexual Stigma, and the Revised Conflict Tactics Scale Short Form. The results showed a positive association between attachment anxiety, and general and psychological SSIPV perpetration. Similarly, attachment avoidance was positively related with general, psychological, and physical SSIPV perpetration. The association between romantic attachment, and general and psychological SSIPV was partially mediated by internalized homonegativity. These findings have theoretical implications and provide valuable information to implement services and interventions tailored for SSIPV, to date scarce and not effective.